الأدب الصوفي من خلال كتاب البُستان لابن مريم التلمساني (ت بعد 1025هـ 1617م - (:unkn) unknown (جامعة الوادي university of Eloued, 2019)
ملخص: يعتبر الادب الصوفي من أرقي وأفضل ألوان الادب العربي و هو بحق ادب رفيع المستوي سواء كان ذلك بسبب عمق افكاره وتنفرد مصطلحاته ومعانية أو من حيث كونه غير نابع من طلب المصلحة الدنيوية فكل اغراضه تدور حول فلك الدين كالحب الالهي والمديح النبوي وغير ذلك من باقي الاغراض الاخرى, كما انه نابع من تجارب وحدانية عميقة عاشها المتصوفة في مختلف الازمان و لهذا فلا نبالغ اذا اعتبرناه من ارقي الوان الادب, ولان كتاب البستان لابن مريم التلمساني قد حفظ لنا ما انتجه صوفية المغرب من ادب صوفي يدخل ضمن هذا الباب فقد خصصناه بالدراسة واستخرجنا كل ما فيه من ادب صوفي وضفناه ضمن اغراضه الخاصة Résumé : La littérature soufie est l’une des couleurs les plus belles et les meilleures de la littérature arabe: c’est vraiment une littérature de haut niveau, que ce soit en raison de la profondeur de ses idées et de ses significations uniques, ou parce qu’elle ne découle pas de la demande de l’intérêt mondial. Et il découle des expériences vécues dans les profondeurs du soufis vécues à des époques différentes. N'exagérez donc pas si nous le considérons comme les plus belles couleurs de la littérature, et parce que le livre du verger du fils de Mary Tlemceni nous a sauvés. Il est extrait de la littérature de Sophie et l'enterré inclus Ses propres fins Abstract:  Sufi literature is one of the finest and best colors of Arabic literature. It is truly a high-level literature, whether because of the depth of its ideas and its unique meanings and meanings, or because it is not derived from the request of the worldly interest. All its purposes revolve around the religion of religion such as divine love and prophetic praise and other other purposes. , And it stems from the experiences of deep in the Sufis lived in different times and so do not exaggerate if we consider it the finest colors of literature, and because the book of the orchard of the son of Mary Tlemceni has saved us what produced Sufism of Morocco literature Sufi enters within this section we devoted to study and extracted everything It is from the literature of Sophie and buried it included His own purposes.
مذكرة ماستر تاريخ تخصص تاريخ الغرب الإسلامي
Keywords: تلمسان، ابن مريم التلمساني، التصوف الإسلامي، الأدب الصوفي، كتاب البستان; Tlemcen, Ibn Maryam Tlemceni, mysticisme islamique, littérature soufie, Le livre de Bustan; Tlemcen, Ibn Maryam Tlemceni, Islamic mysticism, Sufi literature, The Book of Bustan